Bacia hidrográfica do Rio Cuiabá, MT : um estudo da extração da rede de drenagem e delimitação dos seus limites, utilizando modelos digitais de elevação - Santos, Cézar Clemente Pires dos (2013)
Watershed consists of a geographical territorial topographically defined, bounded by the watershed, drained by a watercourse or a connected system of watercourses, such that all flow effluent is discharged through a single outlet. This physiographic unit is considered as the basic unit for environmental management and spatial planning. In the processes of automatic delineation of watersheds in a GIS environment, relevant information is used, represented by Digital Elevation Model (DEM). The objective of this work is the evaluation of the method of extraction and drainage networks Automatic delineation of watersheds using cells quantitative thresholds accumulation of flow in different Digital Elevation Models in a GIS environment, using as study area watershed River Cuiabá MT, located between the parallels 14 ° 18 'and 17 ° 00' S and between meridians 54 ° 40 'and 56 ° 55' W. The results indicated that the Cuiabá River basin bounded by the ASTER sensor has an area of 29,975 km2, has for the SRTM Radar basin has an area of 29,279 km2. The drainage systems extracted from the cells flow accumulation varied between 1629.26 km for standard threshold (1%) 4552.70 km for minimum tested (0.1%) using SRTM, as for sensor networks Aster drainage varied between 1822.80 km for the standard threshold (1%) and 5101.80 km for threshold tested (0.1%). The basin this ranked 5th order according to the methodology proposed by Strahler for ASTER and SRTM radar. The morphometric analyzes indicated that the basin has a low propensity to severe flooding, the drainage density is considered low, indicating that this basin has a lower propensity to flooding, roughness index indicates that the basin has high susceptibility to degradation. The proposed methodology using MDE for watershed delineation and extraction of networks was reliable and easy to use and can be used to morphometric studies in watersheds elsewhere.